Association between NOS3 polymorphisms and osteonecrosis of the femoral head. Issue 1 (4th December 2019) - Zhao, Xiaodong; Yang, Fuqiang; Sun, Luwei; Zhang, Ali
Abstract: Purpose: This study aimed to detect the association between nitric oxide synthase 3 ( NOS3 ) gene polymorphisms (rs1799983 and rs3918181) and the susceptibility to osteonecrosis of the femoral head (ONFH). Methods: Total 88 ONFH patients (55 non-traumatic ONFH and 33 traumatic ONFH) and 90 healthy controls were recruited in this case–control study. Polymerase chain reaction-restriction fragment length polymorphism(PCR-RFLP) was adopted for genotyping NOS3 rs1799983 and rs3918181 polymorphisms. χ 2 test was used to calculate differences in genotype and allele frequencies of NOS3 gene polymorphisms between the cases and controls. Relative risk of ONFH was represented using odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Results: The T allele of the polymorphism rs1799983 showed significantly different frequencies between ONFH patients and control groups ( p = .046) and carrying this allele significantly decreased the disease risk (OR = 0.521, 95%CI = 0.272–0.997), especially for non-traumatic ONFH (OR = 0.408, 95%CI = 0.179–0.929, p = .029). But genotype frequencies of the polymorphism rs1799983 had no obvious difference between the compared two groups ( p > .05 for all). There was no remarkable association between NOS3 rs3918181 polymorphism and NOFH risk ( p > .05 for all). Conclusions: NOS3 rs1799983 polymorphism is obviously associated with ONFH and its T allele may be a protective factor against ONFH occurrence in Chinese Han population.